An Investigation of Marketing Capabilities and Social Enterprise Performance in the UK and Japan. (7th May 2013) - Liu, Gordon; Eng, Teck‐Yong; Takeda, Sachiko
Abstract : The purpose of this article is to extend the existing research on the relationship between eight different types of marketing capability and social enterprise performance. More specifically, we examine third‐sector organizations that have transformed their traditional business model to become more business‐like social enterprises and how these marketing capabilities influence the success of this transformation in both the UK and Japan. We identify, among other things, that not all marketing capabilities are positively associated with social enterprise performance. These findings challenge the conventional wisdom that market‐driven organizations must develop all types of marketing capability. We suggest that social entrepreneurs should develop their marketing capabilities selectively according to their specific performance objectives.